Soil Fertility Dynamics and Xanthomonas Wilt Incidence in Enset (Ensete Ventricosem) Based Farming at Chencha, Southern Ethiopia - Tesfaye, Hajiso Hadaro; Sabura, Shara; Zenebe, Mekonnen Adare (Journal of Agronomy Research, 2025)
Enset (Ensete ventricosum) is a vital food security crop cultivated in South and South-western parts of Ethiopia. However, enset production and the farming families have been threatened by Xanthomonas wilt and its spread in the farming system. Thus, this study was conducted to investigate the soil fertility and plant management practices association on the incidence of Enset Xanthomonas wilt. Data on soils fertility and diseases from enset based farming clustered into inner, outer and outfield farm zone were sampled and surveyed. The result indicated that soil chemical properties significantly (p≤0.05) varied from inner to outfield farm zone. Significantly maximum nutrients store revealed in inner enset farm zones. Disease incidence reduced from inner to the outfield enset farm zone. Disease prevalence and disease incidence scored 28.5% and 11.6%, respectively depending on altitude and genotypes. Soil fertility levels in the enset inner and outfield plots were varied purposely to cultivate enset products as kocho, bulla or amicho (cooking type). The variations in soil fertility and Xanthomonas wilt incidence was associated with management practices applied for desired enset products. Therefore, management practices in enset based farming, soil fertility and location of enset planting zones found to be major indicators for disease incidence addressing to device control interventions.
Keywords: Dynamics; enset management; nutrition; soil fertility; Xanthomonas wilt